Cerebral Amyloid Angiopathy-Related Inflammation: Report of a Case with Very Difficult Therapeutic Management. (16th August 2015) - Crosta, Francesca; Orlandi, Berardino; De Santis, Federica; Passalacqua, Gianni; DiFrancesco, Jacopo C.; Piazza, Fabrizio; Catalucci, Alessia; Desideri, Giovambattista; Marini, Carmine
Abstract : Background . Cerebral amyloid angiopathy-related inflammation (CAA-ri) results from autoimmune response to beta-amyloid deposits in cerebral vessels. Its clinical course and complications have seldom been described in literature. Case Report . In a patient presenting with delirium and left hemiparesis the diagnosis of CAA-ri was supported by the finding of elevated anti-amyloid autoantibodies in the cerebrospinal fluid (CSF). Steroid therapy produced significant improvements in clinical and investigational assessments, but after two months, it caused Acute Respiratory Distress Syndrome. After steroid therapy discontinuation the patient presented a rapidly progressive dementia, Guillain-Barré syndrome, new cerebral ischemic lesions, and thrombosis of the right cephalic and subclavian veins that were treated with subcutaneous heparin. After a week the patient died because of brain hemorrhage. Conclusion . This case suggests caution in steroid therapy discontinuation and antithrombotic therapy administration in patients with CAA-ri. The CSF search of anti-amyloid autoantibodies could be helpful to support the diagnosis.